ANT 2010/11: AWI airborne Accumulation Radar data over western DML and central East Antarctica connecting the EDML and South Pole ice core (WEGAS Project) - Daniel Steinhage; Wilfried Jokat; Veit Helm (PANGAEA, 2025)
This dataset contains airborne radar data acquired using the AWI Accumulation Radar (ACCU) system during the Antarctic season of 2010/11. The profiles cover western Dronning Maud Land, south of the EDML ice core site and connect the EDML ice core site with South Pole. The data are available as netCDF files (including waveforms and metadata), KML files of the profile line locations, and quicklook images of the radargrams.